2012
DOI: 10.1111/mmi.12077
|View full text |Cite
|
Sign up to set email alerts
|

Hyphal heterogeneity in Aspergillus oryzae is the result of dynamic closure of septa by Woronin bodies

Abstract: SummaryHyphae of higher fungi are compartmentalized by septa. These septa contain a central pore that allows for inter-compartmental and inter-hyphal cytoplasmic streaming. The cytoplasm within the mycelium is therefore considered to be a continuous system. In this study, however, we demonstrate by laser dissection that 40% of the apical septa of exploring hyphae of Aspergillus oryzae are closed. Closure of septa correlated with the presence of a peroxisome-derived organelle, known as Woronin body, near the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 59 publications
1
102
0
Order By: Relevance
“…Strain NSRKu70-1-1A, which was constructed by introducing plasmid pAdeA, containing the adeA marker gene, into strain NSRKu70-1-1 (18), was used as a wildtype strain. An Aohex1 disruptant strain, NSK-⌬hex1-1, was obtained by using strain NSRKu70-1-1, as previously described (13), and was used for comparative phenotype analysis in the same genetic background as that for the Aolah disruptant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain NSRKu70-1-1A, which was constructed by introducing plasmid pAdeA, containing the adeA marker gene, into strain NSRKu70-1-1 (18), was used as a wildtype strain. An Aohex1 disruptant strain, NSK-⌬hex1-1, was obtained by using strain NSRKu70-1-1, as previously described (13), and was used for comparative phenotype analysis in the same genetic background as that for the Aolah disruptant.…”
Section: Methodsmentioning
confidence: 99%
“…Although in a limited number of species, including N. crassa, the hexagonal crystal structure of the Woronin body is clearly visible by light microscopy, the fusion of Hex1 with a fluorescent protein is necessary to visualize and track Woronin bodies in most Pezizomycotina species (9,10). Such localization studies have revealed that Woronin bodies reversibly close the septal pore during normal growth and impede the cytoplasmic continuity between adjacent cells, thereby creating hyphal heterogeneity with regard to gene expression activity (13).…”
mentioning
confidence: 99%
“…32) It is important to note that the septal pore is not constitutively open and that fluctuations between the open-closed state is dependent on the behavior of the AoSO protein in response to environmental stress. 33,34) The functional analysis of Woronin body brought a new aspect of biotin biosynthesis. Biotin is an essential cofactor involved in a number of carboxylation and decarboxylation reactions.…”
Section: )mentioning
confidence: 99%
“…Such zonal heterogeneity was also shown previously with respect to gene expression (38)(39)(40)(41)(42)(43)(44) and protein accumulation (39) in A. bisporus. In fact, these processes can be heterogeneous even between neighboring hyphae within a mycelial zone (45)(46)(47)(48)(49). Spectra of neighboring hyphae at the surface and under the peel of the mushroom were also heterogeneous (Fig.…”
Section: Figmentioning
confidence: 99%